Associations of Organizational Safety Practices and Culture With Physical Workload, Perceptions About Work, and Work-Related Injury and Symptoms Among Hospital Nurses. (July 2017) - Lee, Soo-Jeong; Lee, Joung Hee
Abstract : OBJECTIVE: The study aim was to examine the relationships of organizational safety practices with nurses' perceptions about job and risk and experiences of work-related injury and symptoms. BACKGROUND: Nursing professions report high rates of work-related injuries. Organizational safety practices have been linked to workers' safety outcomes and perceptions about work. METHODS: This study analyzed data from a random sample of 280 California RNs in a cross-sectional statewide survey. Data were collected by both postal and online surveys. RESULTS: Higher perceptions of organizational safety practices (safety climate, ergonomic practices, people-oriented culture) were significantly associated with lower physical workload, lower job strain, higher job satisfaction, lower risk perception, and lower work-related injury and symptom experiences. Ergonomic practices and people-oriented culture were associated with less intention of leaving job. CONCLUSIONS: Organizational safety practices may play a pivotal role in improving positive perceptions about jobs, reducing injury risks, and promoting nurse retention.